PENERAPAN REHABILITASI TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DITINJAU DARI UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA (STUDI WILAYAH BANDA ACEH) - Zulhelmi Zulhelmi; Mahmud Mulyadi; Jelly Leviza (Smart Education, 2024)
Abstract: The narcotics problem is a global problem faced by all countries in the world, including Indonesia, although in different contexts and complexities. In an international perspective, narcotics crimes are categorized as serious crimes. The same category also applies in the Indonesian context, which is assessed from the impact it causes and puts narcotics crimes on a par with other serious crimes such as crimes of terrorism and corruption. The research method used in this research is a normative legal research method. The data collection technique is library research, namely through searching scientific documents and books to obtain a theoretical basis in the form of positive legal material that is appropriate to the object to be studied. The aim of rehabilitation punishment for perpetrators of narcotics crimes is in the form of resolving criminal cases using a repressive approach as implemented in the Criminal Justice System, which has given rise to retributive justice, which is oriented towards retribution in the form of punishment and imprisonment.Â Keywords: Rehabilitation, Criminal Act, Narcotics Abstrak: Persoalan narkotika merupakan persoalan global yang dihadapi semua negara di dunia, termasuk Indonesia, meskipun dalam konteks dan kompleksitas yang berbeda-beda. Dalam perspektif internasional, kejahatan narkotika dikategorikan sebagai kejahatan serius. Kategori yang sama juga berlaku dalam konteks Indonesia yang dinilai dari dampak yang ditimbulkan dan membuat kejahatan narkotika disejajarkan dengan kejahatan serius lainnya seperti kejahatan terorisme dan korupsi. Teknik Pengumpulan data adalah penelitian kepustakaan (library research), yaitu melalui penelusuran dokumen-dokumen maupun buku-buku ilmiah untuk mendapatkan landasan teoritis berupa bahan hukum positif yang sesuai dengan objek yang akan diteliti. Tujuan pemidanaan rehabilitasi terhadap pelaku tindak pidana narkotika adalah dalam bentuk penyelesaian perkara pidana dengan menggunakan pendekatan refresif sebagaimana dilaksanakan dalam Sistem Peradilan Pidana, telah melahirkan Keadilan Retrebutif (Retrebutif Justice), yang berorientasi padaÂ pembalasan berupa pemidanaan dan pemenjaraan.Â Kata kunci: Rehabilitasi, Tindak Pidana, Narkotika